The Art of Translation - Levý, Jirí (John Benjamins Pub. Co., 2015)
Jirí Levý's seminal work, The Art of Translation, considered a timeless classic in Translation Studies, is now available in English. Having drawn on adjacent disciplines, the methodology of Czech functional sociosemiotic structuralism and the state-of-the art in the West, Levý synthesized his findings and experience in the field presenting them in a reader-friendly book, which combines the approaches of a theoretician, systemic analyst, historian, critic, teacher, practitioner and populariser. Although focused on literary translation from theoretical, descriptive and historical perspectives, i.